HEMOLYTIC UREMIC SYNDROME - A CASE PRESENTATION - Teodora Adam; Cornel Olimpiu Aldea; Sorin Claudiu Man (Amaltea Medical Publishing House, 2017)
The presentation aims to illustrate in a didactic manner the clinical aspects, laboratory findings and the diagnostic steps in a case of hemolytic uremic syndrome (HUS), also pointing out the importance of differential diagnosis for the triad consisting of microangiopathic hemolytic anemia, thrombocytopenia and acute kidney injury. The clinician's approach regarding the prognostic factors is also depicted, alongside the hallmarks concerning the treatment of HUS, the aspects of acute kidney injury monitoring and the need for a long term follow-up of HUS patients.